A Novel Scheme for Nonlinear Evolution Equations Using Symbolic Computations - Yıldırım, Yakup; Yaşar, Elif; Adem, Abdullahi Rashid; Yaşar, Emrullah (Journal of Applied Nonlinear Dynamics, 2026)
In this study a novel method, namely multiple exponential function scheme is performed for nonlinear evolution equations. Based on ﬁrst order auxiliary equations, one-, two-, and three-wave solutions can be established by using computerized symbolic computations. For illustrating the eﬀectiveness of this approach, we apply the method to solve (3+1) dimensional classical Jimbo-Miwa and it’s extended (3+1) dimensional forms. In addition, we determine dispersion relation and phase shift for each of the models.